Patient Generated Digital Health Data: An Example from the Finnish Neuro Registry - Kuusisto, Hanna; Hämäläinen, Päivi; Nurmi, Henriikka; Kälviäinen, Reetta; Soilu-Hänninen, Merja (Netherlands, 2025)
Patient generated health data is increasingly supported by mobile devices, health applications and patient interfaces, through which it can be shared and forwarded to healthcare professionals (HCPs). The Finnish Neuro Registry, integrated into electronic patient records (EPRs), was developed to monitor neurological disorders. It has numerous sub-registries for specific neurological diseases such as multiple sclerosis (MS) and epilepsy. This article focuses on the patient interface for people with MS (pwMS) as well as the digital seizure diary for people with epilepsy. Patient generated data through the patient interface is displayed on a HCPs' interface to facilitate patient participation in clinical decision making. As of September 2024, the Finnish MS registry, operational for ten years, includes data from 12,633 patients, covering approximately 90% of Finland's MS population. The Finnish epilepsy registry, operational for less than three years, now includes data from 18,325 patients. The existence of the Finnish Neuro Registry is based on close collaboration between healthcare professionals, information technology (IT) specialists, and patients, highlighting the importance of teamwork in achieving seamless data integration and optimizing outcomes.
Envisioning the Future of Health Informatics and Digital Health